The Economics of Socio-Cultural Exclusion: A Behaviorist Perspective - Pati, Uma Charan; Banji, Babita; Rath, Sudhansu Sekhar (International Journal of Psychosocial Rehabilitation, 2020)
India’s focus on inclusive growth in the 12th Five Year Plan paved the way for extensive studies on the state of exclusions and deprivations deep rooted in our socio-cultural milieu. Socio-economic and socio-cultural exclusions can’t be seen solely from the stereotypical canvas of income rather the contemporary stories of deprivations have to be told from the perspective of behavioral economics. Social marginalization is a hindrance which does have an income effect but identity of an individual plays a dominant role in seeing someone as included or deprived of the basic socio-economic and cultural amenities. A case study of three backward villages in the remotest part of the state of Odisha was conducted with the main objectives of exploring how socio-economic and cultural deprivations have been responsible for the low standard of living of the masses in the rural areas and to determine how identity plays an important role in such exclusions of the masses. With the help of descriptive statistics and a dummy independent variable regression model, this particular study has inferred that exclusion of various types and degrees have reasons and also explanation lies mostly in the demand side. Further, behavioral actions and perceptions of the masses must be prioritized while unfolding the real reasons behind such marginalization of the margins.